2022
DOI: 10.1371/journal.pone.0267498
|View full text |Cite
|
Sign up to set email alerts
|

The phytochemical diversity of commercial Cannabis in the United States

Abstract: The legal status of Cannabis is changing, fueling an increasing diversity of Cannabis-derived products. Because Cannabis contains dozens of chemical compounds with potential psychoactive or medicinal effects, understanding this phytochemical diversity is crucial. The legal Cannabis industry heavily markets products to consumers based on widely used labeling systems purported to predict the effects of different “strains.” We analyzed the cannabinoid and terpene content of commercial Cannabis samples across six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 78 publications
2
51
0
Order By: Relevance
“…The current study extends these findings and demonstrates that this inconsistency applies also to the plant’s cannabinoid profile ( Figure 2 and Figure 4 ). This finding provides further support for the proposition that it is essential to adopt scientifically based methodologies for strains’ chemotypic classification in order to generate advanced pharmacological applications for cannabis products [ 72 , 73 , 74 ]. Additionally, our study identified significant interactions between traits associated with three parts of the cannabis plant: the physiology, morphology and phenology of the intact plant; its inflorescence morphology and its cannabinoid profile.…”
Section: Discussionsupporting
confidence: 59%
“…The current study extends these findings and demonstrates that this inconsistency applies also to the plant’s cannabinoid profile ( Figure 2 and Figure 4 ). This finding provides further support for the proposition that it is essential to adopt scientifically based methodologies for strains’ chemotypic classification in order to generate advanced pharmacological applications for cannabis products [ 72 , 73 , 74 ]. Additionally, our study identified significant interactions between traits associated with three parts of the cannabis plant: the physiology, morphology and phenology of the intact plant; its inflorescence morphology and its cannabinoid profile.…”
Section: Discussionsupporting
confidence: 59%
“…Mono- and sesqui-terpenes are the most abundant volatile compounds in Cannabis ( Rice and Koziel, 2015 ; Fischedick, 2017 ; Orser et al, 2018 ) and are thought to be responsible for the characteristic odor of mature and dried flowers. Strain differences in terpene composition have been observed ( Casano et al, 2011 ; Lewis et al, 2018 ; Mudge et al, 2019 ; Smith et al, 2022 ) and crowd-sourced ratings have been used to sort strains according to sensory similarity ( de la Fuente et al, 2020 ). However, the association between specific terpenes and a strain’s aroma profile remains speculative pending definitive studies using gas chromatography-olfactometry as has been done for the cones of the hop plant ( Steinhaus and Schieberle, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated Cannabis chemotypes (the chemical profile of a strain), often with a focus on terpenes, the volatile compounds that are important in creating distinctive strain-specific aromas. Variation in terpene profiles has been documented between strains described as “indica” or “sativa” ( Watts et al, 2021 ), in Cannabis groups defined by the relative abundance of THC and CBD ( Mudge et al, 2019 ; Smith et al, 2022 ), among different regions of the United States ( Smith et al, 2022 ), and in the effects reported by medical Cannabis patients ( Lewis et al, 2018 ). Mudge et al (2019 ) proposed that the diversity of Cannabis aromas observed today is a product of selection for scents believed to be associated with specific THC levels.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, within the Cannabis industry, varieties may be arbitrarily designated as ‘novel’ with little scientific information available regarding the ancestral genetics of each plant and the extreme level of outcrossing or inbreeding that has occurred, often in recent decades. For example, a recent metabolomic analysis of 89,923 samples of dried Cannabis flowers from the Canadian market revealed a disparity between product labeling and secondary metabolite profiles, and directly stemming from this finding, called for a classification and naming system to more accurately represent the diversity of Cannabis varieties [ 16 ]. One recent attempt at this was an analysis of terpene synthase genes which suggested using a set of genetic markers associated with the terpenes as preferable to the modern Cannabis culture labeling of varieties as either ‘ sativa ’ or ‘ indica ’, based on aroma [ 17 ].…”
Section: Discussionmentioning
confidence: 99%